PH sensitive amphiphilic conetworks based on end-group cross-linking of polydimethylsiloxane pentablock copolymer and polymethylhydrosiloxane. Issue 23 (13th March 2015) - Qiu, Ming; Zhao, Xin-Zheng; Liu, Da-Peng; He, Chun-Ju
<x xml:space="preserve">Abstract</x> A series of pH-responsive amphiphilic conetworks were synthesized through cross-linking of well-defined amphiphilic pentablock copolymers via atom transfer radical polymerization.